2015
DOI: 10.1007/s12206-015-0141-y
|View full text |Cite
|
Sign up to set email alerts
|

Copper oxide nano-particles as friction-reduction and anti-wear additives in lubricating oil

Abstract: Lubricants based on hydrocarbon-type mixtures do not satisfy all requirements of OEMs (Original equipment manufacturers) for modern applications. The usual solution is the addition of small amounts of certain additive compounds that render significant improvements in base oil properties such as oxidative degradation, tribological performance and other characteristics. This study examined the tribological behavior of copper oxide nanoparticles as additives in mineral based multi-grade engine oil. All tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(51 citation statements)
references
References 11 publications
(10 reference statements)
1
48
0
2
Order By: Relevance
“…It can be observed that the coefficient of friction increases with increase in load. For a lubricant containing CuO, previous studies reveal that only a thin layer of lubricant can be maintained in the boundary lubrication regime and the direct contact between asperities plays a dominant role (Jatti and Singh 2015). The increase in the coefficient of friction with increase in load is therefore due to the increased interaction between the asperities of two sliding surfaces.…”
Section: Tribological Studiesmentioning
confidence: 98%
“…It can be observed that the coefficient of friction increases with increase in load. For a lubricant containing CuO, previous studies reveal that only a thin layer of lubricant can be maintained in the boundary lubrication regime and the direct contact between asperities plays a dominant role (Jatti and Singh 2015). The increase in the coefficient of friction with increase in load is therefore due to the increased interaction between the asperities of two sliding surfaces.…”
Section: Tribological Studiesmentioning
confidence: 98%
“…Cu NPs and Ag NPs were used as metal cladding modifiers of nanolamellar MoS 2 [144,145] and WS 2 [137] particles. It was demonstrated that such nanocomposite lubricants changed the COF of the original [128] lubricant and significantly improved its wear resistance. In Ref.…”
Section: Nanocompositesmentioning
confidence: 99%
“…Copper‐based engineered nanomaterials (ENMs) are unique among the most widely used ENMs because Cu contains 3 oxidation states (Cu 0 , Cu 1+ , and Cu 2+ ) and exhibits many unique and useful physicochemical properties . In particular, CuO NPs are being widely used in many applications including high‐efficiency catalysts , energy‐saving materials , high‐temperature superconductors , gas sensors , antimicrobial agents , environmental remediation , and friction‐reduction and anti‐wear additives .…”
Section: Environmental Behavior Of Cuo Nps and Asmentioning
confidence: 99%